Respiratory Control Technique and Attention Deficit Hyperactivity Disorder: a Project in a School of the (Portuguese) Second Cycle of Basic Education - Piscalho, Isabel; Catela, David; Victorino, Ana Carolina; Cerekeira, Bárbara; Marques, Nicole; Ferreira, Rita; Dias, Sara (Revista da UI_IPSantarém, 2020)
Attention deficit hyperactivity disorder (ADHD) comprises a persistent pattern of symptoms hyperactivity, impulsiveness and/or lack of attention (cf. APA, 2013), and can cause a significant impairment in academic activities (Cantwell & Baker, 1991), with negative effects on the self-esteem (Matza, Paramore, & Prasad, 2005). ADHD has a prevalence rate ranging from 3% to 7% among school age children (Rowland, Lesesne, & Abramowitz, 2002; Rash & Aguirre-Camacho, 2012). Complementary interventions with children are starting to be used, as Yoga (e.g., Jensen, & Kenny, 2004; Stück, & Gloeckner, 2005), namely because that its breathing techniques may have therapeutic value (e.g., Shannahoff-Khalsa, & Kennedy, 1993; Jella, & Shannahoff-Khalsa, 1993). In fact, school Yoga programs for ADHD children (e.g., Peck, Kehle, Bray, & Theodore, 2005; Abadi, Madgaonkar, & Venkatesan, 2008) and families (e.g., Harrison, Manocha, & Rubia, 2004) is wide-spreading. All the Yoga programs include breathing exercises, based on the reduction of rhythm and on the lengthening of the breathing cycle. Respiratory sinus arrhythmia (RSA) is the variation in heart rate that accompanies breathing. Heart rate increases during inhalation and decreases during exhalation. Cardiac measures have been used to provide external validation of disruptive and non-disruptive attention deficit disorder (e.g., Dykman, Ackerman, & Oglesby, 1992). RSA is higher among children with typical development than in medicated children with ADHD, but unmedicated children with ADHD have the lowest RSA (Buchhorn et al., 2012). Respiratory frequency usually occurs between 9 and 24 breaths/minute. At approximately 6 breaths per minute there is an increase in RSA amplitude, a rhythm that can be achieved with little training (Lehrer, Vaschillo, & Vaschillo, 2000). RSA is important because it determines heart rate variability (HRV); which is assumed to be an index of cardiac autonomic activation, i.e., an outcome variable in breathing training (Lin, Tai, & Fan, 2014), being that its high-frequency component (0,15 to 0,40 Hz) is a marker of parasympathetic nervous system (PNS) (Camm et al., 1996; Reyes del Paso et al., 2013) related to psychological factors including attention and emotion regulation (Thayer & Lane, 2009). This process is possible because heart rate is under tonic inhibitory control peripherally via the vagus (Levy, 1990; Uijtdehagge and Thayer, 2000). Higher levels of resting HRV, compared to lower resting levels, produce context appropriate emotional responses (Ruiz-Padial et al., 2003; Thayer and Brosschot, 2005). Emotion dysregulation is associated with ADHD in children, and is also associated with HRV (Bunford et al., 2017). In fact, ADHD in childhood is associated with abnormal parasympathetic mechanisms involved in emotion regulation (Musser et al., 2011). At the cognitive level, lower resting HRV show larger cortisol responses to mild cognitive challenge that persisted into the recovery period compared to those with high resting HRV (Johnsen et al., 2002). HRV is also positively associated to situational awareness, a critical factor for the central executive to make adequate decisions and actions in stressful and critical situations, which is positively related to performance (Saus et al., 2006). However, children with ADHD present significantly higher mean heart rates, mean R-R interval significantly shorter (lower HRV) and ratio LF/HF significantly higher than children with typical development (Tonhajzerova et al., 2009; Griffiths et al., 2017; Imeraj et al., 2011; Rukmani et al., 2016; cf. de Carvalho et al., 2014). Since HRV is related to both performance and stress responses, our question is if it’s possible to manipulate the HRV of ADHD children, through breath control, to contribute to their performance on academic tasks and capability to adjust to stressful situations. With this purpose, a project was initiated with students, from a public school, identified with potential ADHD. Among the teachers of the potential ADHD children, a Portuguese version of the teacher’s report form (Achenbach, 1991; Fonseca et al., 1995) was applied. At the moment, baseline vital signs (HRV and blood pressure) and the breathing frequency at rest are being collected; and, a training program of breathing, similar, but considerably simpler, to the one proposed by Lehrer, Vaschillo, and Vaschillo (2000), will be implemented for these potential ADHD children. For the abdominal breathing technique training, children are instructed as follows: (1) put one hand on your chest and the other on your belly, (2) breath only through your nose, (3) fill your belly with air, and then let it go out slowly. No attempt was made to control the depth or the pace of breathing, so that everyone will be able to maintain comfortable breathing. HRV data acquisition and recording are carried out through Polar V800 (Giles, Draper, & Neil, 2016). For analysing HRV the gHRV software will be used (Rodríguez-Liñares, Lado, Vila, Méndez, & Cuesta, 2014). Heart rate data is automatically filtered according to Rodríguez-Liñares, Méndez, Vila, and Lado (2012). Frequency domain analysis will be obtained according to Vila et al. (1997). The signal interpolation will be made at 4 Hz, for spectral analysis. The window size and the time shift will be 120 s and 60 s, respectively. Non-linear indexes will be calculated following the algorithms described in Kaplan, Furman, and Pincus (1990) and Pincus and Goldberger (1994). For the analysis of time series, the dimension m and the delay, will be used according Kantz and Schreiber (2004) and Cao (1997), respectively. Data will be statistically treated with program IBM-SPSS, version 24. Shapiro-Wilk test will be used to verify data normal distribution. Wilcoxon test will be used for within group comparison. Effect size r will be calculated (Field, 2013).